2019
DOI: 10.1371/journal.pone.0217760
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mRNA profiles of the exosome-like vesicles in porcine follicular fluid

Abstract: Extracellular vesicles such as exosomes contain several types of transcripts, including mRNAs and micro RNAs (miRNAs), and have emerged as important mediators of cell-to-cell communication. Exosome-like vesicles were identified in the ovarian follicles of several mammalian species. Although the miRNA contents have been extensively characterized, the detailed investigation of their mRNA profiles is lacking. Here, we characterize the mRNA profiles of exosome-like vesicles in ovarian follicles in a pig model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…The study in equine follicular fluid showed that contains microvesicle that carries proteins and miRNAs and some of these miRNAs are present in the surrounding granulosa and cumulus cells suggesting the presence of transfer of bioactive material by microvesicles and exosomes within the follicular microenvironment [72]. The presence of miRNAs in extra cellular vesicles of bovine [28,73], human [74] and porcine [75] follicular fluids indicated the potential roles of EV-mediated miRNAs in folliculogenesis. The expression patterns of the EV-mediated miRNAs depends on follicle size [76] and / or reproductive cycles [77].…”
Section: The Role Of Extracellular Vesicles-mediated Mirnas In Femalementioning
confidence: 99%
“…The study in equine follicular fluid showed that contains microvesicle that carries proteins and miRNAs and some of these miRNAs are present in the surrounding granulosa and cumulus cells suggesting the presence of transfer of bioactive material by microvesicles and exosomes within the follicular microenvironment [72]. The presence of miRNAs in extra cellular vesicles of bovine [28,73], human [74] and porcine [75] follicular fluids indicated the potential roles of EV-mediated miRNAs in folliculogenesis. The expression patterns of the EV-mediated miRNAs depends on follicle size [76] and / or reproductive cycles [77].…”
Section: The Role Of Extracellular Vesicles-mediated Mirnas In Femalementioning
confidence: 99%
“…Their later findings indicated a possible role of exosomes from FF in the regulation of follicle maturation [ 139 ]. CD63-positive EV-mediated cell-cell communication within the follicle was also confirmed in cattle [ 140 ] and in pigs [ 141 ]. Later, the uptake of EVs (CD63-positive) by bovine granulosa and cumulus cells was documented, and EVs were identified in cumulus cells and in transzonal projections [ 142 ].…”
Section: Tetraspanins In Evs Of the Female And Male Reproductive Smentioning
confidence: 90%
“…Other eukaryotic cells can secrete these membrane vesicles, and the quality of exosomes is dependent on the state of the releasing cell [33]. A recent study has suggested that other cells in follicular fluid-like oocytes or theca cells may secrete exosomal-like vesicles, but that the majority originated from mural GCs [34]. Furthermore, exosomes carry proteins and MicroRNAs (miRNAs) [5].…”
Section: Characteristics Of Exosomes and Cell Stressmentioning
confidence: 99%